2012
DOI: 10.1111/j.1476-5381.2012.02010.x
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol promotes non‐rapid eye movement sleep via the benzodiazepine site of the GABAA receptor in mice

Abstract: BACKGROUND AND PURPOSE Decoctions of the Chinese herb houpu contain honokiol and are used to treat a variety of mental disorders, including depression. Depression commonly presents alongside sleep disorders and sleep disturbances, which appear to be a major risk factor for depression. Here, we have evaluated the somnogenic effect of honokiol and the mechanisms involved. EXPERIMENTAL APPROACH Honokiol was administered i.p. at 20:00 h in mice. Flumazenil, an antagonist at the benzodiazepine site of the GABAA rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…In addition, magnolol increased the number of binding sites and the binding affinity on a 1 b 2 g 2 and a 1 b 2 combinations in in vitro saturation binding assays (Ai et al, 2001). Honokiol, another active ingredient of the Chinese herb houpo also does not alter the EEG power density of NREM sleep but increases NREM sleep without effects on REM sleep (Qu et al, 2012). Honokiol enhanced chloride currents through GABA A receptors of seven different subunit compositions and was most effective at those containing a 3 b 2 > a 2 b 2 > a 1 b 2 > a 1 b 1 subunits (Taferner et al, 2011), indicating that magnolol and honokiol may more effective on a 1 and a 3, respectively, than a 2 -containing receptors, and thus have less influence on EEG delta activity of NREM sleep.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, magnolol increased the number of binding sites and the binding affinity on a 1 b 2 g 2 and a 1 b 2 combinations in in vitro saturation binding assays (Ai et al, 2001). Honokiol, another active ingredient of the Chinese herb houpo also does not alter the EEG power density of NREM sleep but increases NREM sleep without effects on REM sleep (Qu et al, 2012). Honokiol enhanced chloride currents through GABA A receptors of seven different subunit compositions and was most effective at those containing a 3 b 2 > a 2 b 2 > a 1 b 2 > a 1 b 1 subunits (Taferner et al, 2011), indicating that magnolol and honokiol may more effective on a 1 and a 3, respectively, than a 2 -containing receptors, and thus have less influence on EEG delta activity of NREM sleep.…”
Section: Discussionmentioning
confidence: 98%
“…The doses of the honokiol were selected with reference to previous studies (Qu et al, 2012;Vavilala et al, 2013). Donepezil hydrochloride was used as the positive control (Xian et al, 2014).…”
Section: Drug Treatmentmentioning
confidence: 99%
“…Honokiol (10 and 20 mg/kg) was found to significantly shorten sleep latency and to increase the amount of non-rapid eye movement sleep, though it had no effect on either the amount of rapid eye movement sleep or EEG power density. This group also found that honokiol excited sleep-promoting neurons in the ventrolateral preoptic areas (49). The sleep-promoting and anxiolytic effects of honokiol suggest a potential additional role for this neolignan in the anesthetic arena.…”
Section: Anxiolysis and Sleepmentioning
confidence: 89%